The Eutrophication of the Baltic Sea has been Boosted and Perpetuated by a Major Internal Phosphorus Source - Stigebrandt, Anders; Andersson, Ambjörn (Frontiers in Marine Science, 2020)
The phosphorus (P) concentration c1 in the surface layer of the Baltic proper in winter depends on the land-based P source LPS, and the ocean P source OPS, which are known. It also depends on the internal P source IPS from anoxic bottoms and the sum of internal and external P sinks TPsink, which are estimated in this paper. IPS is parameterized as fs∙Aanox, where fs is the specific annual mass flux of P from anoxic sediments and Aanox is the area of anoxic bottoms, and TPsink is parameterized as c1∙TRVF, where TRVF is the total removal volume flux. We use a time-dependent P budget model, and 47 years of observational data, and the method of least squares to determine the best estimates of the unknown parameters fs and TRVF. The result is TRVF=3000 km3 year-1 and fs = 1.22 tonnes P km-2 year-1. With these parameter values, the model gives a quite good description of the observed evolution of c1. The observed runaway evolution of c1, with increasing c1 since the 1980s although the land-based supply LPS has been halved, is well described by the model. It is concluded that the internal P source IPS provides a positive feedback mechanism that has boosted and perpetuated the eutrophication of the Baltic proper and that IPS is the major driver of the Baltic Sea eutrophication since the late 1990s. It is suggested that measures to eliminate IPS should be included in the management strategy to reduce the eutrophication of the Baltic proper.